“Defense” injuries in attacks on humans by domestic dog (Canis lupus familiaris) and jaguar (Panthera onca) - de Campos Neto, Manoel Francisco; Junior, Vidal Haddad [UNESP] (Maad Rayan Publishing Company, 2019)
This communication describes two attacks by domestic and wild carnivores in Caceres County, localized in the Pantanal area, an extensive flooded plain in Mato Grosso State, Midwest region of Brazil. The first attack took place in an urban area and was caused by a Rottweiler dog (Canis lupus familiaris) created by the family of the victim. Another attack occurred in a rural area, caused by a jaguar (Panthera onca), which was disturbed while feeding, characterizing an unprovoked attack. Both the patients were wounded in the forearm, with different severity of the wounds. The lesions restricted to the forearm were the consequence of the victims using their arms as a shield, featuring the “defense” injuries, but the severity of the wounds were proportional to the strength of the attacking carnivore. Health staffs and emergency centers should be alert for soft tissue and bone injuries in the observed body regions after domestic and wild animal attacks.
Keywords: Animal bites; Attacks on humans; Domestic animals; Wildlife